Preparation and stability assessment of Perilla frutescens seed oil powder - Chaiyavat Chaiyasut (2018)
© 2017 The Authors. Objective: The present study deals with the preparation and stability assessment of Perilla frutescens seed oil powder (PSOP) by spray drying technique. Methods: Perilla oil emulsion was prepared with various combinations of emulsifiers and maltodextrin powder. The emulsion was dried in a spray dryer, and dried samples were packed and stored at 4, 25, and 40°C for 3 months. The changes in acid and peroxide value the fatty acid content of PSOP during storage were assessed. PSOP samples were subjected to scanning electron microscopic analysis to examine the size and shape of the particle. Results: About 9.52% of PSOP yield was obtained while 5% of whey protein was used as an emulsifier. The moisture content of the PSOP was 2.06 ± 0.23-3.08 ± 0.13%. The acid and peroxide values were increased from 1.49 ± 0.09 to 3.71 mg KOH/g of PSOP, 4.10-7.18 mEq/kg of PSOP, while stored in aluminum foil and kept at 40°C. About 39.97, 26.68, 24.78, and 7.47% of linolenic, oleic, linoleic, and palmitic acids were found in PSOP, respectively. Conclusion: The study revealed that spray-dried PSOP was stable when stored in the absence of light and air at low temperature. The spray-dried PSOP is the best candidate for pharmacological and food applications.